Research progress on potential effects of noise on glycolipid metabolism - Wenjing DU; Haoyan GU; Shan WU (环境与职业医学, 2023)
Noise pollution has become a common public health problem. The harm of noise exposure to human health cannot be ignored. Exposure to noise not only damages the auditory system but also affects the non-auditory system. At present, accumulating domestic and international epidemiological studies have suggested that noise exposure may be related to glycolipid metabolism disturbance. This article summarized recent epidemiological evidence of the association between noise exposure and glucose and lipid metabolism disorders, such as type 2 diabetes, obesity, metabolic syndrome, and hyperlipidaemia. The potential biological mechanisms connecting noise exposure to glucolipid metabolism were also introduced, e.g. noise as a stressor, sleep disorders, and intestinal flora regulation. This study discussed the impacts of noise exposure on glycolipid metabolism related diseases, providing a basis for further identifying noise related risk factors, conducting future related research, and formulating scientific and effective prevention and control measures.